Metal-mediated aminocatalysis provides mild conditions: Enantioselective Michael addition mediated by primary amino catalysts and alkali-metal ions - Leven, Matthias; Neudörfl, Jörg M.; Goldfuss, Bernd (Beilstein Journal of Organic Chemistry, 2013)
Four catalysts based on new amides of chiral 1,2-diamines and 2-sulfobenzoic acid have been developed. The alkali-metal salts of these betaine-like amides are able to form imines with enones, which are activated by Lewis acid interaction for nucleophilic attack by 4-hydroxycoumarin. The addition of 4-hydroxycoumarin to enones gives ee’s up to 83% and almost quantitative yields in many cases. This novel type of catalysis provides an effective alternative to conventional primary amino catalysis were strong acid additives are essential components.
Keywords: alkali metals; aminocatalysis; DFT-calculations; Lewis acids; Michael addition